Os egressos do centro de engenharias e ciências exatas/Foz do Iguaçu: discutindo o perfil e as contribuições no desenvolvimento local e regional - Limanski, Luciana Carla (2022)
Higher education institutions, with the objective of attending and demonstrating the service to their mission, have identified the need to institutionalize research instruments that present their contributions and especially in the territory in which they are inserted and how they are carried out. One of the actions that make it possible to demonstrate their contribution in the place they are inserted is the identification of the current situation of their graduates. In this sense, the present study aimed to identify the profile and analyzed how the training offered by the Center for Engineering and Exact Sciences (CECE) of the State University of the West of the Paraná (UNIOESTE), located at the Foz do Iguaçu campus, contributes to local development. and regionally through its graduates. The qualitative approach research is characterized as a case study and used the questionnaire as a data production instrument. The research sought to answer the guiding question “How does the academic training provided by the Center for Engineering and Exact Sciences (CECE), in partnership with ITAIPU and Itaipu Technology Park (PTI), contribute to the training of professionals and the possible impacts on local and regional development through of your graduates?” and to identify if the partnership between company and university has contributed in the academic formation process, as well as to reflect if the mission of the university is being fulfilled by the graduates of CECE inserted in the job market and in the local and regional society. The survey had the participation of three hundred and fifty-six respondents, graduates on the four undergraduate courses offered by CECE, and it was possible to identify that 77% are male, 81% are aged between 21 and 38 years, 80% continued higher education and today they are established in 11 Brazilian states and abroad, of which 67% are in the state of Paraná and 42% remained in the city of Foz do Iguaçu. In addition, 93% are in the job market and 77% work in the training area, with 30% in management positions/functions and 68% no longer have contact with the university, however 94% would recommend the course to some friend. From the data, it is possible to infer that the academic training provided by the Center for Engineering and Exact Sciences (CECE), in partnership with ITAIPU and PTI, contributed to professional training, in the view of these professionals and that the fact that a large majority of these professionals to remain in the state of Paraná and more specifically in Foz do Iguaçu city contributes to local and regional development.